A produção de saberes em espaços e tempos de aprendizagem colaborativa na formação e no trabalho com arte-educação nas escolas - Costa, Maria Zenilda (2009)
The study argues on the possibilities for constructing knowledge among art-educators within learning processes in different time and settings, to produce collaborative knowledge that can call for other meanings to educational formation, work, and curriculum arts actions in school. Based on a multi-reference approach, the research presents multiple dialogues between rationalities that rely on aesthetical education trajectory in school, stressing the context art-educators’ daily aesthetics, whose formative trajectory and teaching work is showed in distinctions of social taste. The knowledge development paradigm in the multi-reference perspective gathers a heterogeneous co-production from studies and ways established with subjects during the collaborative research-action, with the following desired epistemologically coherent aims: engaging research subjects’ participation as co-producers of knowledge centered in actions within art-education formation and work at school, and the production of knowledge that can provide collaborative learning in art-education practice, which offers formative projects articulated with school culture; reasoning on significant time settings/neighborhoods as well as their potentialities to intensify collaborative learning among art-educators; describing knowledge produced within collaborative learning events and its contribution to instruct and improve art-educators’ teaching practice. Collaborative research-action methodology, whenever it gathers elements of ethnographic and etnomethodologic matrices, constituted the very route of investigation, since it was built along with teachers, the co-producers of knowledge produced. From investigative experiences carried out in Brazil, Canada and England, this study designed steps called co-situation, cooperation, and co-production. Developing investigation based on practical epistemology, gave birth to collaborative research-action as the front door to diminishing the distance between two worlds: the one for teaching practice, and the world of academic production on education research; since the collective production of knowledge from art-educators’ subjectivity augmented possible contributions to teachers’ work and formation within this teaching area. Results show that the construction of collaborative knowledge from heterogeneous nature converges to promoting collaborative learning webs, whereas school community is the focus of aesthetical education. To University fits the role of contributing to the development of a reflexive culture that can engage a variety of settings and time, and placing itself as well as an instructive subject, along with the most diverse cultural spaces.